A base nacional curricular - uma análise à luz da sociolinguística educacional - Zwirtes, Polyana (2020)
The objective of this research is to analyze the Portuguese Language Curricular Component of the final years of Elementary School of the National Curriculum Common Base (2017) (Base Nacional Comum Curricular - BNCC, in Portuguese), verifying if the language practices are articulated with the principles of Educational Sociolinguistics and, if they are articulated, how this is accomplished. The choice of Sociolinguistic theory is due to the understanding of language from its relationship with real subjects, and as a representation of its social, cultural and class transformations. For this, the work is structured in three axes. The first dedicates to contextualizing the process that led to the creation of the BNCC. There has been a proposal for a minimum curriculum since the 1988 Constitution and the 1996 LDB. However, curriculum proposals that have passed through the Brazilian educational system until then were limited to government proposals and suggestions; from the BNCC, approved in 2017, the national curriculum has a normative and mandatory character for all public and private schools of Early Childhood and Basic Education. In addition to this requirement, it is noticeable that the BNCC was built to satisfy some interests that, at times, do not align with the needs of the public school for transformative and emancipatory training. The second axis analyzes curriculum theories present in the formation of the Brazilian curriculum in contrast to the BNCC, which is anchored in curriculum theories - which defend efficiency, the formation of the subject as an uncritical workforce and the evaluation on a large scale - as well as in the Pedagogy of Competences, it presents a false proposal of equal conditions and opportunities for access to education throughout the national territory. However, it does so by making schools and teachers responsible for this guarantee and thereby justifying possible and probable failures in the subjects' adult lives. In the third and final axis, the teaching of Portuguese in Brazil is presented from the Sociolinguistics Educational, in particular. The analysis of the Portuguese Curricular Component for the Final Years of Elementary Education finds that the new curriculum proposal contemplates the presuppositions of Educational Sociolinguistics only apparently. BNCC's curriculum proposal aims to meet the demands of the market and large-scale assessment exams. Through a critical analysis of content from Alves (2000, 2014), Bortoni-Ricardo (2005), Duarte (2010), Ladson-Billings (1995), Lopes and Macedo (2010, 2011), Macedo (2014, 2018), Malanchen (2014), Perrenoud (1999, 2000), Ramos (2006), Silva (2001) we postulate that BNCC is yet another tool for controlling and maintaining the division of classes.